Fikih Journalistic Principles: Deepening Students' Understanding as a Foundation for Social Media Ethics - Fadloli Fadloli; Abdul Chalim; Muhammad Sinal (STAI Syaichona Moh. Cholil Bangkalan, 2022)
Interaction on social media among students has positive and negative impacts, including increasing plagiarism and teenagers becoming anti-social. This article outlines the procedure and instructional strategy for teaching new students at the State Polytechnic of Malang the journalistic fiqh rules. This research results from field research—analysis of research data from interviews, observations and documentation with the reduction stages, display and verification. Journalistic jurisprudence, as the ethical basis for Malang Polytechnic students, carries a universal principle, namely that in social media, one should maintain ethics by not spreading slander, not provoking, not promoting pornography, not gossiping and not using social media to sell prohibited items.